Opressão econômica e violência social: retratos do cotidiano em três parábolas da Fonte Q (Q 12,39-40; 42-46; 19,12-27) - Souza, Ricardo de Oliveira (2008)
In an environment like the one of the first century Galilee, where the teaching was done in the religious communities, villages and family nuclei in an oral way, the method of teachings settlement through the assimilation of daily symbols was fundamental. Due to that, we believe that, among oral or written sources preserved and organized by Synoptic Gospels, Jesus parables compose the most original literary gender because they had been preserved in the memory with greater precision, by Jesus first followers. Many studious have undertaken important works to research the social place of Jesus parables, most of them starting from the own texts disposed as they are in the Gospels. In this paper, we have proposed to work Jesus parables as sayings well preserved by the orality starting from Theory of Q Source, that is treated as one of the most primitive extracts of Synoptic Gospels formative tradition and of Jesus movement. The parables of The Thief , (Q 12,39-40) Unfaithful Servant and (Q 12,42-46) Entrusted Money (Q 19,12-27) have always been seen by the ecclesiastical tradition as parables which treat the necessary surveillance of the Christian because of sudden Jesus parusia. However, this paper intends to say that, much besides, they would treat the social context of first century Galilee, where economical oppression and social violence imposed to the small owners and impoverished farmers are faithfully portrayed.(AU)